A Comparative Survey on Various Coin Recognition Systems Based on Image Processing (International Journal of Engineering and Computer Science, 2013)
Coins are a fundamental need of human life. They are used in everyone’s daily routine, like banks, transport, market and these spare change also has some other uses than getting traded in for cash like for measurement purpose, in games (toss), in organizations for research purpose, etc. So, it holds a great importance that coins can be detected with high accuracy. The Aim of a coin recognition system is to classify high volumes of coins with high accuracy within a short time span. In this paper we present a comparison between various coin recognition systems in terms of their accuracy. Different coin recognition approaches have been proposed by various researchers based on image recognition method. One can easily detect and recognizes coins with the help of these systems. Classification is based on images from both sides and a radius of the coin. On the basis of this literature survey we can say that image processing is the most effective method for coin recognition.